Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1103/physrevc.95.044612
|View full text |Cite
|
Sign up to set email alerts
|

Influence of target deformation and deuteron breakup in (d,p) transfer reactions

Abstract: Background: The effect of core excitations in transfer reactions of the form A(d, p)B has been reexamined by some recent works, using the Faddeev/AGS reaction formalism. The effect was found to affect significantly the calculated cross sections and to depend strongly and non-linearly on the incident deuteron energy.Purpose: Our goal is to investigate these effects within a coupled-channels formulation of the scattering problem which, in addition of being computationally less demanding than the Faddeev counterp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
(59 reference statements)
2
19
0
Order By: Relevance
“…It is found that the cross sections are no longer proportional to the spectroscopic factor and the departure from this proportionality increases with increasing incident energies, reaching a maximum at a deuteron energy of E d ≈60 MeV. Similar results and conclusions were achieved in [114] using two alternative methods. One uses an extended ADWA model, with a deformed adiabatic potential.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…It is found that the cross sections are no longer proportional to the spectroscopic factor and the departure from this proportionality increases with increasing incident energies, reaching a maximum at a deuteron energy of E d ≈60 MeV. Similar results and conclusions were achieved in [114] using two alternative methods. One uses an extended ADWA model, with a deformed adiabatic potential.…”
supporting
confidence: 72%
“…To study the scattering of three-body projectiles, such as Borromean nuclei, the Hamiltonian (105) must be generalized in order to take into account the three-body structure of the projectile. For example, for a two-neutron Borromean system with a structure of the form a = b + n + n one may use the Hamiltonian (114) H = H proj ( x, y)…”
mentioning
confidence: 99%
“…One way to deal with these induced three-body (I3B) terms is to explicitly include excited target states in the reaction model. This has, for example, been done within the CDCC [5,6] and Faddeev [7][8][9] approaches. However, these calculations include explicitly only a fraction of the model space needed to fully account for all the absorption known to be needed in the nucleon optical potentials.…”
mentioning
confidence: 99%
“…Such a behavior is in sharp contrast with transfer reactions [6,7,11,19,20] where dσ/dΩ(0 + ) obtained including the CX cannot be factorized into the SP differential cross section (dσ/dΩ) SP and the associated SF. The size of this CX effect may be characterized by the ratio R = dσ/dΩ(0 + ) SF(0 + ) · (dσ/dΩ) SP (7) or its deviation from unity D = (R − 1) × 100%.…”
Section: Resultsmentioning
confidence: 86%